Mitochondrial genome assembly and comparative analysis of decaploid Camellia hainanica - Zhang, Shihui; Zhang, Yuyan; Luo, Sheng; Gao, Jie; Hu, Haiyan; Liu, Jinping; Wu, Wenqiang; Wang, Jian; Huang, Xiaolong; Lai, Hanggui; Huang, Dongyi (Frontiers in Plant Science, 2025)
IntroductionDecaploid Camellia hainanica is a new tea oil Camellia species discovered in recent years that is unique to Hainan. This species has high nutritional and medicinal value and shows strong adaptability in the growth process. Mitochondria play an important role in plant cells and have an independent genetic system. Therefore, assembling and annotating the mitochondrial genome function of decaploid C. hainanica is of great significance.MethodsThis study successfully assembled the mitochondrial genome of decaploid C. hainanica and comprehensively annotated its functional genes using the Nanopore sequencing platform.ResultsResults showed that the mitochondrial genome is 902,617 bp in length, with a typical circular structure and a guanine–cytosine content of 45.79%. The genome encodes 64 protein-coding genes and contains a total of 76 genes, including 40 mRNA, 32 tRNA, 3 rRNA, and 1 pseudogene. Tetranucleotide repeats accounted for 38.60% of the simple sequence repeats. Only two genes, atp6 and sdh4, had a Ka/Ks ratio <1, whereas the Pi value of the sdh3 gene had a maximum of 0.00374 in these regions, suggesting that the sdh3 gene can be used as a molecular marker for the analysis of the mitochondrial genome of C. hainanica. From the relative synonymous codon usage (RSCU) analysis, 29 codons had RSCU values >1, 27 of which (93%) ended in A or U, indicating a bias for A/U endings is present in C. hainanica. During RNA editing, 48.24% (260 loci) of amino acids were changed from hydrophilic to hydryophobic, resulting in an increase in the hydrophobicity of the protein. Comparative analysis identified 34 homologous fragments between the mitochondrial and chloroplast genomes, with the longest fragment being 9,572 bp in length. Phylogenetic analysis of the genomes showed that the Hainanese and Vietnamese varieties of tea oil Camellia are sister species.DiscussionResults confirmed that the mitochondrial genomes of Hainanese and Vietnamese tea oil Camellia underwent gene rearrangement. Results also provided key data support for the utilization and conservation of tea oil germplasm resources and the breeding of varieties and are of great significance for promoting genetic evolution research, genetic breeding, and identification of tea oil Camellia.